2022
DOI: 10.1007/s12550-022-00456-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of ochratoxin A, 2′R-ochratoxin A and citrinin in human blood serum from Switzerland

Abstract: Biomonitoring of mycotoxins and their metabolites in biological fluids is increasingly used to assess human exposure. In this study, biomarkers of ochratoxin A (OTA) and citrinin (CIT) exposure were determined in a large number of serum samples from healthy blood donors in Switzerland. In 2019, 700 samples from different regions were obtained. From 240 donors, a second sample (taken 2–9 months later) was available for analysis. Moreover, 355 blood donor samples from 2005 from all regions in Switzerland and 151… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The toxicity of citrinin is further worsened by the fact that it usually occurs along with other mycotoxins, especially OTA and AFB 1 , as they are produced by the same species of fungi. It mostly occurs with OTA, with both synergistically exerting nephrotoxic effects, and may have influence on necrosis and apoptosis in hepatocytes (Gayathri et al, 2015 ; Jaus et al, 2022 ). Many in vitro studies showed that citrinin toxicity involves decreased cytokine production nitride oxide gene expression's inhibition, increase in ROS, inhibition of DNA and RNA synthesis, oxidative stress induction, and apoptotic cell death activation through the caspase cascade system and signal transduction pathways (European Food Safety Authority, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The toxicity of citrinin is further worsened by the fact that it usually occurs along with other mycotoxins, especially OTA and AFB 1 , as they are produced by the same species of fungi. It mostly occurs with OTA, with both synergistically exerting nephrotoxic effects, and may have influence on necrosis and apoptosis in hepatocytes (Gayathri et al, 2015 ; Jaus et al, 2022 ). Many in vitro studies showed that citrinin toxicity involves decreased cytokine production nitride oxide gene expression's inhibition, increase in ROS, inhibition of DNA and RNA synthesis, oxidative stress induction, and apoptotic cell death activation through the caspase cascade system and signal transduction pathways (European Food Safety Authority, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Citrinin and its metabolite (dihydrocitrinon) have been detected in urine by Ali et al ( 2015 ) in 82% and 84% of urine samples, respectively. Citrinin mostly targets the kidney (Jaus et al, 2022 ). These toxic effects of citrinin and other mycotoxins can be prevented by treating foods and feeds using HPAS in citric acid concentration adjusted to pH 4.5 or 4.0 or below prior to further processing and/or consumption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIT has similar structural and toxicological characteristics to those of OTA [3]. With the kidney being the primary target organ in some mammalian species [8],The simultaneous occurrence for them raised concerns about the potential risks to human and animal health [9]. When focusing on their combined toxicity [10] Previous studies have shown synergistic or additive effects of these nephrotoxins [10,11].…”
Section: Introductionmentioning
confidence: 99%